Interventions for visual field defects in people with stroke - Pollock, Alex (Cochrane Database Syst Rev, 2019)
BACKGROUND: Visual field defects are estimated to affect 20% to 57% of people who have had a stroke. Visual field defects can affect functional ability in activities of daily living (commonly affecting mobility, reading and driving), quality of life, ability to participate in rehabilitation, and depression and anxiety following stroke. There are many interventions for visual field defects, which are proposed to work by restoring the visual field (restitution); compensating for the visual field defect by changing behaviour or activity (compensation); substituting for the visual field defect by using a device or extraneous modification (substitution); or ensuring appropriate diagnosis, referral and treatment prescription through standardised assessment or screening, or both. OBJECTIVES: To determine the effects of interventions for people with visual field defects after stroke. SEARCH METHODS: We searched the Cochrane Stroke Group Trials Register, the Cochrane Eyes and Vision Group Trials Register, CENTRAL, MEDLINE, Embase, CINAHL, AMED, PsycINFO, and PDQT Databse, and clinical trials databases, including ClinicalTrials.gov and WHO Clinical Trials Registry, to May 2018. We also searched reference lists and trials registers, handsearched journals and conference proceedings, and contacted experts. SELECTION CRITERIA: Randomised trials in adults after stroke, where the intervention was specifically targeted at improving the visual field defect or improving the ability of the participant to cope with the visual field loss. The primary outcome was functional ability in activities of daily living and secondary outcomes included functional ability in extended activities of daily living, reading ability, visual field measures, balance, falls, depression and anxiety, discharge destination or residence after stroke, quality of life and social isolation, visual scanning, adverse events, and death. DATA COLLECTION AND ANALYSIS: Two review authors independently screened abstracts, extracted data and appraised trials. We undertook an assessment of methodological quality for allocation concealment, blinding of outcome assessors, method of dealing with missing data, and other potential sources of bias. We assessed the quality of evidence for each outcome using the GRADE approach. MAIN RESULTS: Twenty studies (732 randomised participants, with data for 547 participants with stroke) met the inclusion criteria for this review. However, only 10 of these studies compared the effect of an intervention with a placebo, control, or no treatment group, and eight had data which could be included in meta‐analyses. Only two of these eight studies presented data relating to our primary outcome of functional abilities in activities of daily living. One study reported evidence relating to adverse events. Three studies (88 participants) compared a restitutive intervention with a control, but data were only available for one study (19 participants). There was very low‐quality evidence that visual restitution therapy had no effect on visual field outcomes, and a statistically significant effect on quality of life, but limitations with these data mean that there is insufficient evidence to draw any conclusions about the effectiveness of restitutive interventions as compared to control. Four studies (193 participants) compared the effect of scanning (compensatory) training with a control or placebo intervention. There was low‐quality evidence that scanning training was more beneficial than control or placebo on quality of life, measured using the Visual Function Questionnaire (VFQ‐25) (two studies, 96 participants, mean difference (MD) 9.36, 95% confidence interval (CI) 3.10 to 15.62). However, there was low or very‐low quality evidence of no effect on measures of visual field, extended activities of daily living, reading, and scanning ability. There was low‐quality evidence of no significant increase in adverse events in people doing scanning training, as compared to no treatment. Three studies (166 participants) compared a substitutive intervention (a type of prism) with a control. There was low or very‐low quality evidence that prisms did not have an effect on measures of activities of daily living, extended activities of daily living, reading, falls, or quality of life, and very low‐quality evidence that they may have an effect on scanning ability (one study, 39 participants, MD 9.80, 95% CI 1.91 to 17.69). There was low‐quality evidence of an increased odds of an adverse event (primarily headache) in people wearing prisms, as compared to no treatment. One study (39 participants) compared the effect of assessment by an orthoptist to standard care (no assessment) and found very low‐quality evidence that there was no effect on measures of activities of daily living. Due to the quality and quantity of evidence, we remain uncertain about the benefits of assessment interventions. AUTHORS' CONCLUSIONS: There is a lack of evidence relating to the effect of interventions on our primary outcome of functional ability in activities of daily living. There is limited low‐quality evidence that compensatory scanning training may be more beneficial than placebo or control at improving quality of life, but not other outcomes. There is insufficient evidence to reach any generalised conclusions about the effect of restitutive interventions or substitutive interventions (prisms) as compared to placebo, control, or no treatment. There is low‐quality evidence that prisms may cause minor adverse events.